Spatial and temporal variability of the productivity of coffee canephora - Lima, Juliao Soares de Souza; Costa, Felipe Pianna; Xavier, Alexandre Candido; Oliveira, Rone Batista; Silva, Samuel Assis (Coffee Science - ISSN 1984-3909, 2014)
GIS techniques have been used in many agricultural crops to study and assess the causes of spatial and temporal variability in production. The spatial and temporal variability of the canephora (conilon) coffee productivity was analyzed in the present work in three consecutive agricultural years (harvests) using geoprocessing techniques. A sampling grid with 109 georeferenced points was built with five plants per point. Significant differences in productivity were observed, with the lowest productivity recorded for the harvest 3 in 93.5% of the area. The productivity index (YI) varied from -18.0% in harvest 2 to harvest 1 and from -57.0% in harvest 2 to harvest 3, showing increasing decrease between different harvests.